A Workbook on Planning for Urban Resilience in the Face of Disasters: Adapting Experiences from Vietnam's Cities to Other Cities - Shah, Fatima (World Bank, 2015)
This Workbook offers a step-by-step guide for city officials in proactively planning for natural disasters and climate change impacts. It is based on learning from three cities in Vietnam - Ha Noi, Can Tho, and Dong Hoi ? that developed Local Resilience Action Plans (LRAPs) containing a set of prioritized actions, related to both infrastructure as well as policy/ regulatory and socioeconomic actions. These LRAPs are based on vulnerability and risks assessments, a gaps analysis drawing on an inventory of planned investments and policy changes, and multi-stakeholder priority setting. The on-the-ground learning from these pilot cities in Vietnam has paved the way for cities in China, Indonesia, and the Philippines to embark on similar processes. This Workbook is a complement to the best-selling Climate Resilient Cities: A Primer on Reducing Vulnerabilities to Disasters (2009).